DESAIN TERUMBU KARANG BUATAN DENGAN METODE AKRESI MINERAL PADA SISTEM AQUARIUM - Wasis Widyanto, Salasi; Radhitia Prasetiawan, Nanda (Universitas Pancasakti Tegal, 2023)
Function of coral reefs is being a living place for marine biota and as protectors from abrasion and sedimentation, so that conservation, protection, and rehabilitation are needed. Among the many rehabilitation technologies developed is artificial coral reefs by mineral accretion methods for insitu conservation. The implementation that is only insitu application is behind the author to make artificial coral reef designs with similar methods for exsitu conservation. The purpose is to make available media for coral nurseries quickly that have quality of strength and resilience before being applied insitu, facilitating research on corals that can grow and survive on these media, and minimize the taking of some coral in the sea for aquascape lovers. The method used refers to engineering technical instructions at the Agency for the Assessment and Application of Technology. The result is the design of artificial coral reefs with 8 mm diameter iron material as a cathode and coconut shell charcoal mixture with cement as an anode. An iron beam frame is 15 cm long, 10 cm wide, and 5 cm high. The required power supply must have an output of 0,380 Ampere at 6 Volt DC voltage, so the required resistance value is 15,78 Ohm. The conclusion is that the design of artificial coral reef with the mineral accretion method in the aquarial system was successfully made after calculating the amount of electric current in the biorock element considered safe for marine biota in the aquarium.